Thermal management and biocompatibility in dry machining: An experimental study of ZrO2-based cutting tool for bone machining - Addepalli, Phanindra; Sawangsri, Worapong; Saiful Anwar, Che Ghani (Elsevier B.V., 2025)
This paper aims to assess the thermal properties and biocompatibility of zirconia-based bio ceramic cutting tools for bone surgery compared to stainless steel (SS316L) tools. Because of their biocompatibility, materials such as zirconia (ZrO2) are now widely utilized to reconstruct and replace bone tissue. The study compares wet and dry machining to analyze the effects of temperature and cell behaviour. By performing a quantitative MTT (yellow 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium-bromide) proliferation assay, the current study showed that ZrO2 had higher cell viability and metabolic activity than SS316L. The experiments included primary chondrocyte cells from chicken femoral condyles incubated at 37 °C and 5 % CO2 with increased cell survival and proliferation in the presence of ZrO2. Thermal performance was evaluated on a CNC vertical milling machine with the help of K-type thermocouples to measure the maximum (Tmax) and average (Tmean) temperature. ZrO2-based tools had resulted in lower Tmax and Tmean throughout the experiment regardless of the cutting parameters, which minimize the thermal injury and improve surgical results. Saline irrigation in wet machining helped in reducing temperature peaks, while dry machining had the advantages of not polluting the environment and being cheaper. Due to its low thermal conductivity and hardness, ZrO2 can be used as an effective material for metal tools in surgical operations to minimize thermal effect and increase the tool lifespan.